Analisis Kualitas Kerajinan Bambu pada Produk Tumbler di Pt. Bintang Mitra Kencana dengan Menggunakan Tujuh Alat Pengendali Kualitas - Irna Nurfadilah; Widya Retno Prasinta (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to analyze the quality of tumbler products at PT Bintang Mitra Kencana and identify factors that influence the occurrence of defects in products. The research method used is a quantitative method with a descriptive research design. Data was collected through documentation and interviews with two informants who were the General Director and production staff at the company. This research uses several Seven Tools quality control tools (check sheets, histograms, Pareto diagrams, control charts, scatter diagrams, stratification diagrams, and cause-and-effect diagrams), as well as attribute control charts (P Chart). The research results show that the most common defects in tumbler products in the company are powder pest defects. Factors that cause defects include a lack of understanding by the workforce regarding raw material care, a lack of clear methods and procedures in the production process, the use of wet raw materials, the use of poorly maintained machines, and an unclean storage environment. Several efforts to improve human factors require training and education for employees, increased supervision and monitoring during the production process. For method factors, it is necessary to develop clear operational standards and appropriate process parameters. For raw material factors, it is necessary to carry out proper drying and appropriate storage. For engine factors, it is necessary to carry out routine maintenance and periodic cleaning. And for environmental factors, it is necessary to arrange a suitable storage environment. By carrying out the recommended corrective actions, it is hoped that we can reduce the level of defects in tumbler products at PT Bintang Mitra Kencana and improve overall product quality.